1982
DOI: 10.1119/1.12738
|View full text |Cite
|
Sign up to set email alerts
|

Teaching problem-solving in physics: A course in electromagnetism

Abstract: In order to improve the teaching and learning situation in the course Electromagnetism for first-year students at the Twente University of Technology, this course has been reconstructed. The main activity in the reconstruction has been directed towards developing means and instructional procedures helpful to the students in learning how to tackle problems in electromagnetism. Therefore a model of the process of solving such problems has been developed and a system of actions and methods appropriate to this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Explicitly modeling an organized set of problem-solving steps and reinforcing this framework throughout a course results in higher course performance [92,115,175,176]. Often such frameworks are based on the work of the mathematician Polya [177]: understand the problem, plan the solution, execute the plan, and look back [73,178,179] but are expanded to include explicit guidelines for constructing an initial description of the problem.…”
Section: Instructional Strategiesmentioning
confidence: 99%
“…Explicitly modeling an organized set of problem-solving steps and reinforcing this framework throughout a course results in higher course performance [92,115,175,176]. Often such frameworks are based on the work of the mathematician Polya [177]: understand the problem, plan the solution, execute the plan, and look back [73,178,179] but are expanded to include explicit guidelines for constructing an initial description of the problem.…”
Section: Instructional Strategiesmentioning
confidence: 99%
“…Research indicates that when instructors explicitly model and encourage students to follow a set of problem solving strategies explicating expert-like behavior, students are likely to adapt a more expert-like problem-solving approach [5,[7][8][9][10][11][12]. These strategies are also referred to in the literature [9] as prescriptive problem solving strategies.…”
Section: A Promoting Expert-like Problem Solving Approachesmentioning
confidence: 99%
“…Helping students develop an expert-like problem solving approach is an important instructional goal for the introductory physics courses, valued both by physics instructors [1][2][3], as well as stake holders in academics and industry [4]. Indeed, instructional strategies have been developed and shown to help students improve their problem solving skills [5][6][7][8][9][10][11][12][13][14][15]. For example, the research comparing novice and expert problem solvers has identified expert-like approaches to problem solving involving elements such as initial problem analysis, planning ahead the solution, and ongoing evaluation of the progress made in the solution accompanied by refinement of the solver's understanding of the principles and concepts involved [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Van Weeren et al (1982), a partir del modelo desarrollado inicialmente por Mettes et al (1980) denominado programa de acciones y métodos (PAM), cuya adaptación al ámbito del electromagnetismo resultaba, en palabras de los autores, excesivamente extenso y detallado, proponen una estrategia de resolución de problemas denominada aproximación sistemática a la resolución de problemas, (SAP), que consiste básicamente en la transformación de los problemas cuantitativos en problemas estándar, a través de tres fases: Fase 1: Lectura razonada del problema. Análisis cuidadoso de los datos y de las incógnitas, representándolos esquemáticamente.…”
Section: Modelos Algorítmicos De Resolu-ción De Problemasunclassified